Structural Characterisation of Hierarchically Porous Silica: Monolith by NMR Cryo-porometry and -diffusometry - Hwang, Seungtaik; Valiullin, Rustem; Haase, Jürgen; Smarsly, Bernd M.; Bunde, Armin; Kärger, Jörg (Diffusion Fundamentals, 2017)
A systematic NMR cryo-porometry and -diffusometry study using nitrobenzene as a probe liquid is carried out in order to characterise pore structures of hierarchically-organised porous silica monolith possessing mesopores along with a 3D bicontinuous macropore network. The result obtained from NMR cryoporometry shows the presence of a relatively wide mesopore size distribution of 10-35 nm. Furthermore, NMR cryodiffusometry indicates that whilst the mesopores are highly tortuous (Tmeso ≈6), they have little influence on the overall tortuosity of the material (Tmacro ≈1.5), which is largely dominated by the macropores (Toverall ≈1.7).